Universalism: Global Evidence - Alexander W. Cappelen; Benjamin Enke; Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper presents a new set of stylized facts about the global variation in universalism, leveraging hypothetical money allocation tasks deployed in representative samples of 64,000 people from 60 countries. Our data reveal large variation in universalism within and across countries, which almost entirely reflects heterogeneity in people's moral views regarding how to treat different types of relationships. These moral views vary systematically with age, gender and religiosity. Universalism is strongly predictive of relevant outcomes such as civic engagement and left-wing economic and social policy views, in particular in the rich West. Across countries, universalism varies with the economic, political and religious organization of societies. We provide tentative evidence that experience with democracy makes people more universalist. Overall, our results show that moral universalism shapes and is shaped by politico-economic outcomes across the globe.
Keywords: 330; universalism; morality; culture